Moth-eye-inspired antireflective structures in hybrid polymers: depth-variable etching techniques, optical performance, thermal stability, and hydrophobicity - Werner, Lukas; Diao, Zhaolu; Spatz, Joachim P.; Abend, Marcus; Resche, Steffen; Hagen, Nico; Busch, Richard; Brunner, Robert (Nanomaterials, 2025)
Hybrid polymers combine the benefits of inorganic and organic material properties, offering superior thermal, mechanical, and chemical stability, making them ideal for optical applications. This study focuses on the fabrication and characterization of antireflective (AR) structures within hybrid polymers using reactive ion etching (RIE). The etching process produces nanopillars with controlled heights, achieving excellent AR performance across a broad spectral range from 450 nm to 2 µm. Optical characterization, including angle-resolved transmission and reflection measurements, shows that the structured samples maintain high transmission efficiency and reduced reflectance at varying incidence angles. Thermal stability tests reveal that the AR structures preserve their optical properties after exposure to temperatures up to 250 °C. Higher temperatures cause significant material yellowing, which is attributed to changes in the bulk material rather than damage to the structured surface. Hydrophobicity measurements show significant water repellency in structured samples, with contact angles more than twice those of unstructured layers. These findings highlight the potential of hybrid polymers with moth-eye-inspired nanostructures for high-performance, durable optical components in demanding environments.
Gesehen am 02.10.2025